Hubungan Faktor Risiko Usia Dengan Angka Kejadian Kanker Payudara Dan Tumor Jinak Payudara Di RSUD Wangaya Kota Denpasar Tahun 2019-2022: The Correlation Between Age Risk Factors And Incidence Rates Breast Cancer And Benign Breast Tumors In Hospitals Wangaya City Of Denpasar In 2019-2022 - Gatsu, Putu Denny Andreana; Cahyani, A. A. Eka; Candra D, I Dewa Gede; Novitasari, Novitasari (Borneo Journal of Medical Laboratory Technology, 2023)
Breast cancer is a condition in which there is a loss of control and normal mechanisms in cells, which causes abnormal, uncontrolled, and rapid growth in breast/mammae tissue. One of the risk factors for the occurrence of breast cancer is age, where a person's risk of being diagnosed with breast cancer will continue to increase as a person gets older and peaks at the age of 80 years. In this study to analyze the correlation between age risk factors on the incidence of breast cancer and benign breast tumors. Analytical observational study with a cross-sectional design. The population is all medical record data for the diagnosis of breast cancer and benign breast tumors at the Wangaya Regional General Hospital, Denpasar City in January 2019 – December 2022. Samples were taken using a categorical descriptive method and analyzed using Chi-square. The highest frequency of breast cancer patients was at the age of 46 - 55 years, amounting to 20 patients (64.5%). The highest frequency of patients with benign breast tumors was at the age of 26-35 years, amounting to 24 patients (30.76%). Chi-square test results show that the probability value (p) <0.05 (p = 0.000). There is a significant correlation between age risk factors and the incidence of breast cancer and benign breast tumors at the Wangaya Regional General Hospital, Denpasar City.